ORANG ASLI TEMUAN MUSIC PORTAL - ABDUL GANI, MOHD TAUFIQ AQMAL (Universiti Teknologi PETRONAS, 2009)
Long before the development of modem science, indigenous peoples which known as Orang Asli in Malaysia have developed their ways of knowing how to survive and also of ideas about meanings, purposes and values. They gathered knowledge for two purposes: survival and meaning. Their knowledge which can be interpreted as indigenous knowledge have been handed down through the generations especially music. Due to various kind of indigenous music, the scope of this study only limited Orang Asli Temuan people and their music. Term of Temuan referred to an ethnic group of Orang Asli in Malaysia. Traditionally, Orang Asli Temuan music has been inherited generation by generation of Orang Asli Temuan people through word of mouth. Unfortunately, this method has exposed risk of losing this knowledge due to the knowledge only be kept in minds of Orang Asli Temuan music experts only. The challenge indicates a part of knowledge leaking from Orang Asli Temuan people where knowledge should be stored, enriched and passes their next generations. It is crucial for Malaysian to understand Orang Asli Temuan music as part of Malaysian heritage. As an initiative to document Orang Asli Temuan music, a prototype of knowledge based portal has been developed to ensure the longevity of the knowledge. Hence, the uniqueness of Orang Asli Temuan able to appreciated by Malaysian as part of Malaysian heritage. Through this understanding and respecting different cultures in Malaysia especially Orang Asli Temuan music, harmony among Malaysian able to preserved. The purpose of this report paper is to capture knowledge of Orang Asli Temuan music and to share knowledge in a knowledge based portal that is called 'Orang Asli Temuan Music Portal'. The report presents how the portal works and benefits everyone; how efficient the proposing features can support and encourage users to share their knowledge. The paper also reviews some researches on the Malaysian and Australian web portals that applied the same concept as 'Orang Asli Temuan Music Portal' to help bring a deeper understanding towards improvement in the knowledge based portal. i